2008
DOI: 10.1007/s10384-008-0525-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical signs and characteristics of pigmentary glaucoma in Chinese

Abstract: In these Chinese patients with PG, homogeneous increased trabecular pigmentation, dusting of the peripheral lens or zonule with pigment granules, and posterior bowing of the iris were common. Typical spoke-like radial TIDs were not observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Mid peripheral iris transillumination defect was not present in any of the cases. Because Asians have thicker irises with denser pigmentation than Caucasians [ 7 ], the mid peripheral iris transillumination defect may not be detected unless there is a high degree of pigment dispersion [ 4 ]. In addition, because there are individual differences in the iris thickness and pigmentation even among Asians [ 8 ], the mid peripheral iris transillumination defect will probably be present only if pigment dispersion occurs in eyes with thin and lower density of pigmentation in the iris.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mid peripheral iris transillumination defect was not present in any of the cases. Because Asians have thicker irises with denser pigmentation than Caucasians [ 7 ], the mid peripheral iris transillumination defect may not be detected unless there is a high degree of pigment dispersion [ 4 ]. In addition, because there are individual differences in the iris thickness and pigmentation even among Asians [ 8 ], the mid peripheral iris transillumination defect will probably be present only if pigment dispersion occurs in eyes with thin and lower density of pigmentation in the iris.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because there are individual differences in the iris thickness and pigmentation even among Asians [ 8 ], the mid peripheral iris transillumination defect will probably be present only if pigment dispersion occurs in eyes with thin and lower density of pigmentation in the iris. A retrospective study of 21 Chinese patients with PDS or PG reported that all of the patients had pigmentation on the trabecular meshwork and posterior corneal pigmentation (Krukenberg spindle) [ 4 ]. We assumed that these two signs were used for the diagnosis of PDS and PG because mid peripheral iris transillumination defect was found in only one patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty one eyes of 11 Chinese (9 males, 2 females) participants in this study identified as PDS and received LPI or trabeculectomy including iridectomy from January to December of 2005 were included in this study. The diagnostic criteria for PDS included at least 2 of the following 3 signs: homogeneous moderate to heavy TM pigmentation (≥Scheie II), lenticular/zonular pigment granule dusting, and corneal endothelial pigmentation in a Krukenberg spindle pattern [3,16,17] . PDS eyes with 2 or more of the following signs were diagnosed with PG: initial IOP > 21mmHg, glaucomatous optic nerve damage (increased cupping or glaucomatous disk appearance), or visual field defect.…”
Section: Methodsmentioning
confidence: 99%
“…The diagnostic criteria for PDS included at least 2 of the following 3 signs: homogeneous moderate to heavy TM pigmentation (≥Scheie II), lenticular/zonular pigment granule dusting, and corneal endothelial pigmentation in a Krukenberg spindle pattern. [3,16,17] PDS eyes with 2 or more of the following signs were diagnosed with PG: initial IOP > 21mmHg, glaucomatous optic nerve damage (increased cupping or glaucomatous disk appearance), or visual field defect. Exclusion criteria included a history of uveitis, trauma, previous ocular surgery or anterior segment laser treatment, or any evidence of exfoliation material.…”
Section: Methodsmentioning
confidence: 99%